The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1080/00140138408963501
|View full text |Cite
|
Sign up to set email alerts
|

Performance and sensory aspects of work in cold environments: a review

Abstract: Performance and sensory aspects of work in cold environments: a review Climatic Physiology and Psychophysiological Sections, De~artment of Occu~ational Medicine. National Board of ~L c u~a t i o n a l safeti and Health, ~1 7 i 84 Solna, SwedenMany people are occupationally exposed to cool or cold environments in which human performance and comfort may be affected. Research results on manual function and other performance measures together with certain subjective efiects relevant to work in moderate cold are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(32 citation statements)
references
References 111 publications
1
31
0
Order By: Relevance
“…As a result, the blood flow to the extremities is reduced even when the hand is exposed to mildly cold temperatures such as 15-25 0 C. (Daanen, 1997). The reduction in blood flow may be the cause for losses in tactile sensitivity , reduced manual performance, grip strength (Holewijn and Heus, 1992;Giesbrecht et al, 1995;Geng 2001, Powell et al, 2000 and increased risk of accidents (Enander, 1984; 4 Havenith et al, 1995;Heus et al, 1995;Geng et al, 2001). Morton and Provins (1960) have found that tactile sensitivity is an L-shaped function of skin temperature and that each individual has a relatively sharp critical temperature at which performance deteriorates significantly.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the blood flow to the extremities is reduced even when the hand is exposed to mildly cold temperatures such as 15-25 0 C. (Daanen, 1997). The reduction in blood flow may be the cause for losses in tactile sensitivity , reduced manual performance, grip strength (Holewijn and Heus, 1992;Giesbrecht et al, 1995;Geng 2001, Powell et al, 2000 and increased risk of accidents (Enander, 1984; 4 Havenith et al, 1995;Heus et al, 1995;Geng et al, 2001). Morton and Provins (1960) have found that tactile sensitivity is an L-shaped function of skin temperature and that each individual has a relatively sharp critical temperature at which performance deteriorates significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Cold impairs physical and mental performance in many ways. Muscle co-ordination and manual dexterity are impaired, physical load is increased, strength and velocity are decreased and postural sway is increased by cold exposure [3,4,5]. Mental performance is also affected, especially performance in complex tasks [6,7,8].…”
Section: Cold Workmentioning
confidence: 99%
“…Manual dexterity is frequently used to evaluate hand function and is important during hand manipulation. Hand/finger skin temperature is considered a vital factor in dexterity (Schiefer et al, 1984;Enander, 1984;Enander & Hygge, 1990;Brajkovic & Ducharme, 2003, Chen et al, 2010 and hand performance (Riley & Cochran, 1984;Havenith et al, 1995, Chen et al, 2010. More importantly, such impairment may lead to an increased number of accidents (Müller, 1982; cited by Havenith et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to cold environments and contact with cold materials have been reported impair tactile sensitivity in the hands (Enander, 1984), hand dexterity (Schiefer et al, 1984;Riley & Cochran, 1984;Enander & Hygge, 1990;Heus et al, 1995), and tracking performance (Goonetilleke & Hoffmann, 2009). Manual dexterity is frequently used to evaluate hand function and is important during hand manipulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation